Tafsir Al-Qur'an Surat:Fathir, Yasin, ash-Shaffat, Shad, az-Zumar, Ghafir, Fushshilat, Asy-Syura, as-Zukhur,ad-Dukhan,al-Jatsiyah, al-Ahqaf, Muhammad, al-Fath, al-Hujurat, Qaf - Syaikh Abdurrahman bin Nashir as-Sa\'di (Darul Haaq, 2016)
vi + 638hlm.; 23 cm